Habitual exercise levels are associated with cerebral amyloid load in presymptomatic autosomal dominant Alzheimer's disease. Issue 11 (11th May 2017) - Brown, Belinda M.; Sohrabi, Hamid R.; Taddei, Kevin; Gardener, Samantha L.; Rainey‐Smith, Stephanie R.; Peiffer, Jeremiah J.; Xiong, Chengjie; Fagan, Anne M.; Benzinger, Tammie; Buckles, Virginia; Erickson, Kirk I.; Clarnette, Roger; et al.
Abstract: Introduction: The objective of this study was to evaluate the relationship between self‐reported exercise levels and Alzheimer's disease (AD) biomarkers, in a cohort of autosomal dominant AD mutation carriers. Methods: In 139 presymptomatic mutation carriers from the Dominantly Inherited Alzheimer Network, the relationship between self‐reported exercise levels and brain amyloid load, cerebrospinal fluid (CSF) Aβ42, and CSF tau levels was evaluated using linear regression. Results: No differences in brain amyloid load, CSF Aβ42, or CSF tau were observed between low and high exercise groups. Nevertheless, when examining only those already accumulating AD pathology (i.e., amyloid positive), low exercisers had higher mean levels of brain amyloid than high exercisers. Furthermore, the interaction between exercise and estimated years from expected symptom onset was a significant predictor of brain amyloid levels. Discussion: Our findings indicate a relationship exists between self‐reported exercise levels and brain amyloid in autosomal dominant AD mutation carriers.